Cost of illness of patient-reported adverse drug events: a population-based cross-sectional survey. Issue 6 (13th June 2013) - Gyllensten, Hanna; Rehnberg, Clas; Jönsson, Anna K; Petzold, Max; Carlsten, Anders; Andersson Sundell, Karolina
Abstract : Objectives: To estimate the cost of illness (COI) of individuals with self-reported adverse drug events (ADEs) from a societal perspective and to compare these estimates with the COI for individuals without ADE. Furthermore, to estimate the direct costs resulting from two ADE categories, adverse drug reactions (ADRs) and subtherapeutic effects of medication therapy (STE). Design: Cross-sectional study. Setting: The adult Swedish general population. Participants: The survey was distributed to a random sample of 14 000 Swedish residents aged 18 years and older, of which 7099 responded, 1377 reported at least one ADE and 943 reported an ADR or STE. Main outcome measures: Societal COI, including direct and indirect costs, for individuals with at least one self-reported ADE, and the direct costs for prescription drugs and healthcare use resulting from self-reported ADRs and STEs were estimated during 30 days using a bottom-up approach. Results: The economic burden for individuals with ADEs were (95% CI) 442.7 to 599.8 international dollars (Int$), of which direct costs were Int$ 279.6 to 420.0 (67.1%) and indirect costs were Int$ 143.0 to 199.8 (32.9%). The average COI was higher among those reporting ADEs compared with other respondents (COI: Int$ 442.7 to 599.8 versus Int$ 185.8 to 231.2). The COI of respondents reporting at least one ADR or STE was Int$ 468.9 to 652.9. Direct costs resulting from ADRs or STEs were Int$ 15.0 to 48.4. The reported resource use occurred both in hospitals and outside in primary care. Conclusions: Self-reported ADRs and STEs cause resource use both in hospitals and in primary care. Moreover, ADEs seem to be associated with high overall COI from a societal perspective when comparing respondents with and without ADEs. There is a need to further examine this relationship and to study the indirect costs resulting from ADEs.